Nilai Wasathiyah Islam dalam Tafsir Lokal Berbahasa Sunda (Studi Atas Kitab Ayat Suci Lenyepaneun) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the contextualization of wasathiyyah values in the Tafsir of the Holy Verse Lenyeupaneun by Moh. Emon Hasim and its relevance for strengthening Islamic brotherhood, national unity, and human solidarity. This study employs a qualitative approach using library research combined with thematic (maudhu’i) tafsir analysis. The primary data sources are the Qur’an and Tafsir Ayat Suci Lenyeupaneun, while secondary data include classical and contemporary tafsir works as well as academic literature on Islamic moderation. The analysis is carried out descriptively and analytically by examining Moh. Emon Hasim’s interpretations and comparing them with other exegetical views, resulting in a comprehensive understanding of the uniqueness of Sundanese local tafsir in actualizing wasathiyyah values. This study concludes that Tafsir Ayat Suci Lenyeupaneun by Moh. Emon Hasim successfully integrates the values of wasathiyyah with Sundanese local wisdom while demonstrating the relevance of Islamic moderation in religious and national life. The values of wasathiyyah presented include balance, tolerance, justice, and brotherhood, which are proven to address religious, national, and humanitarian challenges in Indonesia.